Role of oral probiotic supplementation on gut permeability in obesity: A systematic review of randomized controlled trials - Alpha Fardah Athiyyah; Triska Susila Nindya; Reza Gunadi Ranuh; Andy Darma; Khadijah Rizky Sumitro; Purwo Sri Rejeki; Lilik Djuari; Subijanto Marto Sudarmo; Rina Agustina (Food Hydrocolloids for Health)
Background: Obesity is a chronic condition and a global epidemic, associated with impaired intestinal permeability owing to dysbiosis. Gut microbiota reportedly plays a potential role in obesity treatment. Probiotics have emerged as the most widely used approach for treating dysbiosis. This study explored the effect of oral probiotic supplementation on intestinal permeability in individuals with obesity. Methods: A Systematic review was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses. PubMed, ScienceDirect, PLOS One, and Cochrane databases were searched to identify articles published between 2014 and September 2024. The Cochrane risk-of-bias tool for randomized trials was used to assess publication bias. Results: A total of 690 human RCTs (randomized controlled trials) were identified, of which nine were eligible for this review. Probiotics (Akkermansia, Bifidobacterium, Enterococcus, Lactobacillus, Streptococcus, and a combination of Saccharomyces yeast) used for over 8 weeks may decrease gut permeability outcomes, including plasma zonulin, fecal zonulin, plasma or serum LPS, urinary lactulose, and urinary mannitol; however, BMI (body mass index) levels exhibited inconsistent measurements across all groups. Conclusions: Probiotic supplementation for a minimum of 8 weeks may reduce gut permeability. However, further studies are required to develop standardized protocols for probiotic strains, dosages, durations, and delivery methods, to better understand their effects on intestinal permeability and related outcomes in individuals with obesity.